ANALISIS TEBAL PERKERASAN LENTUR PADA APRON PANGKALAN UDARA SAUMLAKI DI TANIMBAR MALUKU - Muhammad Fahmi Tri Susilo; Achmad Pahrul Rodji; Lydia Darmiyanti (Fakultas Teknik Universitas Krisnadwipayana, 2022)
Currently, Maluku Province is one of the provinces in Indonesia that is experiencing significantdevelopment. This condition affects the number of use of commercial aviation services that will enter and leaveour area both now and in the future. The air base is one of the air bases in the Tanimbar Islands, Maluku Provincewhich currently serves domestic flights. This air base uses a single runway which is the simplest configurationwith a capacity of 7-12 movements per day in VFR (Visual Flight Rules) conditions and 7-10 movements per dayin IFR (Instrument Flight Rules) conditions. The analysis of the flexible pavement thickness of the apron at theSaumlaki Air Base aims to determine the thickness of the pavement layer at the Air Base. The planning methodused is the FAA (Federal Aviation Administration) method. The first step that needs to be considered is the CBR(California Bearing Ratio) value of the subgrade, the determination of the modulus of subgrade value, theselection of the plan plane, the MTOW of the aircraft, the load of one aircraft wheel (W2), corrected departure(R2), the load of one wheel of the aircraft plan (W1 ) and equivalent annual deparatures of the planned aircraft(R1). This pavement thickness analysis uses Boeing 737-900ER and C-130 plan aircraft. Based on the dataobtained, then the plan plane MTOW value, the modulus of subgrade and R1 values are plotted on the FAA curveso that the pavement thickness is obtained, the results of this study indicate that for the plan aircraft Boeing 737-900ER and C-130 required 9.22 cm thick surface coarse and 100 cm base coarse layer with a total pavementthickness of 109.22 cm. The results with this comparison COMFAA application required a surface coarsepavement thickness of 8.4 cm and a base coarse layer of 100 cm with a total pavement thickness of 108.